Understanding the LCA and ISO water footprint: A response to Hoekstra (2016) "A critique on the water-scarcity weighted water footprint in LCA". (January 2017) - Pfister, Stephan; Boulay, Anne-Marie; Berger, Markus; Hadjikakou, Michalis; Motoshita, Masaharu; Hess, Tim; Ridoutt, Brad; Weinzettel, Jan; Scherer, Laura; Döll, Petra; Manzardo, Alessandro; Núñez, Montserrat; et al.
Abstract: Water footprinting has emerged as an important approach to assess water use related effects from consumption of goods and services. Assessment methods are proposed by two different communities, the Water Footprint Network (WFN) and the Life Cycle Assessment (LCA) community. The proposed methods are broadly similar and encompass both the computation of water use and its impacts, but differ in communication of a water footprint result. In this paper, we explain the role and goal of LCA and ISO-compatible water footprinting and resolve the six issues raised byHoekstra (2016) in "A critique on the water-scarcity weighted water footprint in LCA". By clarifying the concerns, we identify both the overlapping goals in the WFN and LCA water footprint assessments and discrepancies between them. The main differing perspective between the WFN and LCA-based approach seems to relate to the fact that LCA aims to account for environmental impacts, while the WFN aims to account for water productivity of global fresh water as a limited resource. We conclude that there is potential to use synergies in research for the two approaches and highlight the need for proper declaration of the methods applied.